Ultrasound Characteristics of In Utero Infection - Karoline S. Puder; Marjorie C. Treadwell; Bernard Gonik (Hindawi Limited, 1997)
In utero infection of the fetus has become recognized as an important cause of fetal and neonatal morbidity and mortality. Since both anatomic and functional abnormalities have been described in the fetus related to various infections, ultrasonography may be a valuable diagnostic tool in this regard. A complete review of the current literature was undertaken to report available information on this topic. Common pathogens or clinical conditions were selected. The identified data were confounded by the way in which each case originally presented for study. Although certain anomalies were frequently associated with individual organisms, their incidence could not be determined, nor were most specific to that infectious agent. Representative ultrasound images are presented for common and unusual cases.